Peer coaching: a constructivist methodology for enhancing critical thinking in postgraduate business education - Ladyshewsky, Richard (Routledge, 2006)
Peer coaching (PC) is one experiential learning method that can be used to enhance the depth of learning in managerial education. The paper explores the concept of peer coaching, and reports on the experiences of 43 students who participated in a PC program as part of their postgraduate management education. Powerful learning effects are reported by participants, and characteristics for successful PC relationships are examined.